Kant on ethics and politics - Ramet, Sabrina P. (Eastern Review, 2019)
Best known for his ethical works, Immanuel Kant was part of the liberal Enlightenment and addressed most of the principal political issues of his day. Several of his major works were written in the wake of the storming of the Bastille in Paris, while Europe was engaged in the French Revolutionary Wars. His rejection of revolution but endorsement of the principles for which the French revolutionaries were fighting, as well as his plea for a federation of European states that would settle disputes peacefully, reflected his engagement with the controversies raised by the Revolution. But, although he could not countenance revolution, he declared that, once a revolutionary government has succeeded in establishing itself, citizens should obey the new government, rather than try to restore the ousted authorities.